Nanoscale Tungsten-Microbial Interface of the Metal Immobilizing Thermoacidophilic Archaeon Metallosphaera sedula Cultivated With Tungsten Polyoxometalate - Milojevic, Tetyana; Albu, Mihaela; Blazevic, Amir; Gumerova, Nadiia; Konrad, Lukas; Cyran, Norbert (Frontiers in Microbiology, 2019)
Inorganic systems based upon polyoxometalate (POM) clusters provide an experimental approach to develop artificial life. These artificial symmetric anionic macromolecules with oxidometalate polyhedra as building blocks were shown to be well suited as inorganic frameworks for complex self-assembling and organizing systems with emergent properties. Analogously to mineral cells based on iron sulfides, POMs are considered as inorganic cells in facilitating prelife chemical processes and displaying “life-like” characteristics. However, the relevance of POMs to life-sustaining processes (e.g., microbial respiration) has not yet been addressed, while iron sulfides are very well known ubiquitous mineral precursors and energy sources for chemolithotrophic metabolism. Metallosphaera sedula is an extreme metallophilic and thermoacidophilic archaeon, which flourishes in hot acid and respires by metal oxidation. In the present study we provide our observations on M. sedula cultivated on tungsten polyoxometalate (W-POM). The decomposition of W-POM macromolecular clusters and appearance of low molecular weight W species (e.g., WO) in the presence of M. sedula have been detected by electrospray ionization mass spectrometry (ESI-MS) analysis. Here we document the presence of metalloorganic assemblages at the interface between M. sedula and W-POM resolved down to the nanometer scale using scanning and transmission electron microscopy (SEM and TEM) coupled to electron energy loss spectroscopy (EELS). High-resolution TEM (HR-TEM) and selected-area electron diffraction (SAED) patterns indicated the deposition of redox heterogeneous tungsten species on the S-layer of M. sedula along with the accumulation of intracellular tungsten-bearing nanoparticles, i.e., clusters of tungsten atoms. These results reveal the effectiveness of the analytical spectroscopy coupled to the wet chemistry approach as a tool in the analysis of metal-microbial interactions and microbial cultivation on supramolecular self-assemblages based on inorganic metal clusters. We discuss the possible mechanism of W-POM decomposition by M. sedula in light of unique electrochemical properties of polyoxometalates. The findings presented herein highlight unique metallophilicity in hostile environments, extending our knowledge of the relevance of polyoxometalates to life-sustaining processes, understanding of transition of polyoxometalates as inorganic prebiotic model to life-sustainable material precursors and revealing biogenic signatures obtained after the decomposition of an artificial inorganic compound, which previously was not associated with any living matter.